Respostas
respondido por:
3
f(3)=3a+b=5
f(-2)=-2a+b=-5
Sistema:
3a+b=5
-2a+b=-5
--------------
5a=10
a=10/5
a=2
3a+b=5
6+b=5
b=5-6
b=-1
f(-2)=-2a+b=-5
Sistema:
3a+b=5
-2a+b=-5
--------------
5a=10
a=10/5
a=2
3a+b=5
6+b=5
b=5-6
b=-1
respondido por:
0
f(x) =a x + b
f(3) = 3 a + b
5 = 3 a + b
f(x) = a x + b
f(-2) = -2 a + b
-5 = -2 a + b
3 a + b = 5
-2 a + b = -5 multiplicando por -1
2 a - b = 5
3 a + b = 5
----------------
5 a = 10
a = 10/5
a = 2
substituindo o valor de a
3 a + b = 5
3.2 + b = 5
6 + b = 5
b = 5 - 6
b = -1
Resposta os valores de a é 2 e de b = -1
f(3) = 3 a + b
5 = 3 a + b
f(x) = a x + b
f(-2) = -2 a + b
-5 = -2 a + b
3 a + b = 5
-2 a + b = -5 multiplicando por -1
2 a - b = 5
3 a + b = 5
----------------
5 a = 10
a = 10/5
a = 2
substituindo o valor de a
3 a + b = 5
3.2 + b = 5
6 + b = 5
b = 5 - 6
b = -1
Resposta os valores de a é 2 e de b = -1
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás